The National Role of KH. A. Abdul Wahid Hasyim in Keeping the Nation Integrity - Muhammad Syaiful Muhtar (Journal of Nahdlatul Ulama Studies, 2021)
This article examines the national role of KH. A. Wahid Hasyim, especially at the beginning of Indonesia's independence. This study is motivated by the scarcity of studies related to the contribution of figures from Islamic boarding schools in national studies, and at the same time the role of this figure is recognized in the form of an award as a national hero. This is library research with analytical descriptive analysis techniques. The research findings showed that at the young age, the national role of KH. A. Wahid Hasyim appears in his efforts to maintain the unity and integrity of Indonesia through his moderate Islamic thinking, neither right nor left extreme. This was proven by his position as one of the independence committees (BPUPKI), and one of his policies was to approve the elimination of seven words in the Jakarta Charter agreement.